2003
DOI: 10.1002/jcb.10603
|View full text |Cite
|
Sign up to set email alerts
|

Cell death in cultured human Saos2 osteoblasts exposed to low‐density lipoprotein

Abstract: Osteoporosis (OP) and atherosclerotic-cardiovascular diseases (and possibly dementia) constitute emerging age-related co-morbidity states that might share risk factors. Blood-born lipids, like LDL involved in atherosclerosis and apolipoprotein-E4 (ApoE4) involved in dementia, may also be implicated in development of OP. We examined osteoblast cell lines as a culture model for OP by exposure to lipoproteins. ApoE expression in Saos2 and U2OS osteoblasts was confirmed by PCR. ApoE4 did decrease cell counts relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 54 publications
2
24
1
Order By: Relevance
“…The effect of TRIM63 overexpression is consistent with previous reports on the global effects of glucocorticoids on human bone marrow stromal cells and SaOS2 cells [7,[10][11]. According to the previous report, glucocorticoids suppressed the proliferation and promoted osteoblastic differentiation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The effect of TRIM63 overexpression is consistent with previous reports on the global effects of glucocorticoids on human bone marrow stromal cells and SaOS2 cells [7,[10][11]. According to the previous report, glucocorticoids suppressed the proliferation and promoted osteoblastic differentiation.…”
Section: Discussionsupporting
confidence: 91%
“…In SaOS2 cells, stimulation with glucocorticoids suppresses growth and promotes activity of alkaline phosphatase, a differentiation marker of the osteoblasts [10,11]. In this study, we performed a comprehensive mi-NheI and ClaI, and ligated into pTRE2puro vector.…”
mentioning
confidence: 99%
“…Although lipid oxidation has been noted in other tissues with advancing age (30), our findings are the first to document an age-related increase in lipoxygenase expression and lipid oxidation in the murine skeleton. That lipid oxidation has negative effects on osteoblasts was previously suggested by in vitro evidence that oxidized low density lipoprotein stimulates apoptosis of osteoblastic cells (73,74) and that oxidized palmitoylarachidonyl-phosphatidylcholine inhibits BMP-2-induced osteoblast differentiation (75). The ROS/FoxO/PPAR␥/␤-catenin cascade elucidated here is most likely responsible for such anti-osteogenic effects because BMP-2-induced osteoblastogenesis depends on Wnt signaling (76).…”
Section: Discussionmentioning
confidence: 51%
“…Accordingly, we (6) and others (20,29) have reported that oxLDL particles induce the apoptosis of osteoblastic cells followed by annexin V staining, DNA fragmentation, loss of lysosomal integrity, and appearance of pro-apoptotic proteins. Furthermore, increasing concentrations of oxysterols such as 7␤-hydroxycholesterol and 7-ketocholesterol resulted in the reduction of MG-63 cell viability (from 20 -30 M) as indicated by the loss of MTT activity after 48 h of incubation.…”
Section: Determination Of Hormesis-like Effects Induced By Oxldl and mentioning
confidence: 77%